Efektivitas Beberapa Jenis Insektisida Nabati Terhadap Hama Kutu Beras (Sitophilus oryzae L.) pada Beras Siam - Djaya, Adrianson Agus; Zendrato, Desrahmat; Pandriyani; Melhanah; Supriati, Lilies (LPPM Universitas Palangka Raya, 2024)
This research was conducted to determine the effectiveness of using several type of botanical insecticides and types of botanical insecticides that are more effective against rice weevil pests (Sitophilus oryzae L.) on siam rice. The method used in this research was the Completely Randomized Design (CRD) method which consisted of 6 treatments, each of which was repeated 4 times so that there were 24 experimental units. The treatment is a type of botanical insecticide consisting of P0 = Control (no botanical insecticide), P1 = 7.5 g of breadfruit leaf flour, P2 = 7.5 g of guava leaf flour, P3 = 7.5 g of noni leaf flour, 5 g, P4 = 7.5 g kaffir lime leaf flour and P5 = 7.5 g papaya leaf flour. The results of the research showed that several types of botanical insecticides used, namely breadfruit leaves, guava, noni and papaya, were not effective in controlling rice weevil pests (≤50%) but had the ability to reduce mortality, efficacy and speed of death of rice weevil pests (Sitophilus oryzae L.) and loss of rice weight. The most effective type of botanical insecticide in controlling the rice weevil pest (Sitophilus oryzae L.) is kaffir lime leaves with efficacy and mortality values ​​of 68.75%, pest death rate of 0.69% and rice weight loss percentage 0%.